Excited cluster states: A new source for proton number fluctuations in the high baryon density regime - Boris Tomášik; Marcus Bleicher (Physics Letters B)
We calculate the contribution of the decay products of excited nuclear cluster states to the event-by-event fluctuations of protons in the energy range from sNN=2−5 GeV within the statistical model. We find that the inclusion of the excited nuclear clusters yields corrections to all cumulant ratios, ranging from 1% for ratio of second to first-order cumulant to 100% for the sixth to second order cumulant towards the lowest inspected energy. As expected the contribution of excited cluster states is most important at low energies sNN<3.5 GeV and becomes negligible at higher collision energies. Especially in light of the expected ultra-high precision data from CBM at FAIR, this new contribution is important to allow for a quantitative comparison with (potentially later available) lattice QCD or effective model results.